Advances in Reclamation and Management of Sodic Waters for Irrigation: Management of sodic waters for irrigation - Choudhary, OP; Mavi, MS (Journal of Soil Salinity and Water Quality, 2023)
Sustainable management of water resources is an international priority to meet the demands of future populations for food and fiber. However, increasing demands for freshwater use for municipal and industrial processes coupled with increasing world food needs leaves very less fresh water available for agriculture. Thus, agriculture will either need to reduce acreage under irrigation, which is undesirable since it will reduce food supply, or irrigate with alternative water sources such as saline/sodic ground waters. This is possible but sustained use of poor-quality water requires consideration of their impacts on both crop production and soil health. In different states of India, 32-84% ground waters surveyed are saline and/or sodic. Injudicious use of sodic waters poses grave risks of causing irrigation-induced sodification that is insidious and impacts soil health in terms of deteriorating soil physical, chemical and biological parameters. The development of salinity and sodicity problems not only reduces crop productivity but also limits the choice of crops. It is, therefore, imperative that plans are carefully drawn and executed to sustain crop production, reduce soil sodification and minimize deterioration of soil conditions over the long-term. In this context, it has been observed in many instances that water previously considered unsuitable for irrigation can be used with site-specific and careful management. In Punjab, about 42% ground waters are brackish and about 70% of these are sodic waters having high sodium absorption ration (SAR) as well as residual sodium carbonate (RSC), posing a serious threat to sustainable crop production, especially in the south-western region of the state. To prevent the degradation of the state’s land and water resources, emerging technological interventions for optimally using sodic-waters for supplementing irrigated agriculture are of paramount importance. In this context, the long-term research work carried over more than three decades has developed many technologies for judicious use of sodic-waters for sustaining crop productivity and maintaining soil health in these challenging environments. Remedial technologies have been developed at the, root-zone, crop and cropping systems, and field scale. These include conjunctive uses based on available water qualities, chemical amelioration of sodic- soils and irrigation waters, mobilising native calcite through organic amendments, growing tolerant crop cultivars, fertiliser use, and irrigation management technologies. Although the emphasis is placed on managing sodic waters in the Indian context, the developed practices are expected to be helpful to promote irrigation with sodic waters, thereby partly alleviating the forecasted scarcities in water for agriculture in many other arid and semi-arid regions in the world confronting similar challenges.